Analysis on the synchronized network of Hindmarsh-Rose neuronal models. (March 2015) - Feng, Youceng; Li, Wei
Abstract: We studied a network of pulse-coupled Hindmarsh-Rose neurons and discovered that all that matters for the onset of complete synchrony is the number of signals, k, received by each neuron. This is independent of all other details of the network structure.